The Eating Disorder Inventory in the screening for DSM-5 binge eating disorder. (August 2016) - Mustelin, Linda; Kärkkäinen, Ulla; Kaprio, Jaakko; Keski-Rahkonen, Anna
Abstract: Background: We assessed whether the Eating Disorder Inventory (EDI) is suitable for screening binge eating disorder (BED) in young women. Method: Young women (N = 2825) from the 1975–79 birth cohorts of Finnish twins were assessed by questionnaires, including subscales of the EDI. For a subset of women (N = 548), we established DSM-5 diagnoses of BED; 16 women had lifetime BED. We compared screening properties of the EDI scales using receiver operating characteristic (ROC) analysis, determined optimal cutoff points, and calculated sensitivities and specificities. Results: The best screen for DSM-5 BED was the global score of three subscales (Bulimia, Drive for Thinness, Body Dissatisfaction) with an area under the curve (AUC) of 0.86. Its sensitivity was 87% and specificity 76% at cutoff ≥ 21. Three individual subscales had acceptable screening properties: Bulimia (AUC 0.83; sensitivity 80%, specificity 78% at cutoff ≥ 2), Drive For Thinness (AUC 0.82; sensitivity 87%, specificity 72% at cutoff ≥ 7), and Body Dissatisfaction (AUC 0.81; sensitivity 93%, specificity 60% at cutoff ≥ 8). Conclusion: The EDI performed well as a screening tool for BED in our community-based sample of young twin women. Future studies should assess its value in other populations and in clinical settings. Highlights: We tested the Eating Disorder Inventory as a screen for DSM-5 binge eating disorder among women in a community-based cohort. The global score of three subscales (Bulimia, Drive for Thinness, Body Dissatisfaction) had the best screening properties. It had an area under the curve (AUC) of 0.86 and its sensitivity was 87% and specificity was 76% at cutoff ≥ 21. The three individual subscales also had acceptable screening properties.